2006
DOI: 10.1128/jcm.00553-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transcription-Mediated Amplification and PCR Assay Results for Various Genital Specimen Types for Detection of Mycoplasma genitalium

Abstract: Mycoplasma genitalium is now recognized as a possible cause of several idiopathic sexually transmitted disease (STD) syndromes. However, due to the difficulty of culture of this fastidious bacterium, nucleic acid amplification tests (NAATs) are necessary for its detection in patient specimens. In the current study we compared a newly developed research-only transcription-mediated amplification (TMA) assay (Gen-Probe Incorporated) to our in-house DNA-based PCR assay for detection of M. genitalium. The relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
77
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 43 publications
10
77
1
2
Order By: Relevance
“…Thus, we are able to determine only a relative sensitivity within the context of our own assay rather than absolute sensitivity and specificity. However, our results are very similar to those of Wroblewski et al, who determined relative sensitivities of vaginal, endocervical, and urine specimens not only by their laboratory's PCR assay but also by the Gen-Probe research-only transcription-mediated amplification assay (13). The implications of these findings are several.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Thus, we are able to determine only a relative sensitivity within the context of our own assay rather than absolute sensitivity and specificity. However, our results are very similar to those of Wroblewski et al, who determined relative sensitivities of vaginal, endocervical, and urine specimens not only by their laboratory's PCR assay but also by the Gen-Probe research-only transcription-mediated amplification assay (13). The implications of these findings are several.…”
supporting
confidence: 77%
“…Our study is the first to compare the utility of urine, cervical, vaginal, and rectal specimens for the detection of M. genitalium by NAATs in women, although one published study has compared vaginal, cervical, and urine specimens (13) and another has compared cervical and urine specimens for M. genitalium detection (6).…”
mentioning
confidence: 99%
“…In the realm of laboratory diagnosis, initial studies of target capture-based transcription-mediated amplification (TMA) in females reported 87.8% (14) We recently demonstrated the utility of TMA-based M. genitalium detection in male specimens originating from both STI and community outpatient clinics (16). In contrast, previous studies of M. genitalium TMA in females have largely focused on high-risk demographics (14,15,(17)(18)(19). Assessment of M. genitalium detection rates in a communitywide setting would be beneficial.…”
Section: T He Sexually Transmitted Infection (Sti) Agentmentioning
confidence: 75%
“…Currently, examination by PCR is the method of choice for the detection of M. genitalium and the most published target genes are major adhesin MgPa genes or 16S rRNA gene. 1,9,16 The most sensitive clinical samples for testing M. genitalium in females when PCR is used, according to the study performed by Wroblewski et al, 17 is from the vaginal swab (91%) compared to the cervical smear (53%) and urine (65%). However, the vaginal smear examination has not been approved by the Food and Drug Administration.…”
Section: Discussionmentioning
confidence: 99%